Good Studies Evaluate the Disease While Great Studies Evaluate the Patient: Development and Application of a Desirability of Outcome Ranking Endpoint for Staphylococcus aureus Bloodstream Infection. (12th October 2018) - Doernberg, Sarah B; Tran, Thuy Tien Tram; Tong, Steven Y C; Paul, Mical; Yahav, Dafna; Davis, Joshua S; Leibovici, Leonard; Boucher, Helen W; Corey, G Ralph; Cosgrove, Sara E; Chambers, Henry F; Fowler, Vance G; et al.
Abstract: Background: Desirability of outcome ranking (DOOR) is an innovative approach in clinical trials to evaluate the global benefits and risks of an intervention. We developed and validated a DOOR endpoint for Staphylococcus aureus bloodstream infection (BSI) through a survey to infectious diseases clinicians and secondary analysis of trial data. Methods: We administered a survey of 20 cases of S. aureus BSI, asking respondents to rank outcomes by global desirability. Correlations and percentage of pairwise agreement among rankings were estimated to inform development of a DOOR endpoint, which was applied to 2 prior S. aureus BSI trials. The probability that a patient randomly assigned to experimental treatment would have a better DOOR ranking than if assigned to control was estimated. Results were also analyzed using partial credit, which is analogous to scoring an academic test, assigning 100% to the most desirable outcome, 0% to the least, and "partial credit" to intermediate ranks. Results: Forty-two recipients (97%) completed the survey. The DOOR endpoint fitting these rankings ( r = 0.89; 95% confidence interval, 0.67 to 0.94) incorporated survival plus cumulative occurrence of adverse events, cure, infectious complications, and ongoing symptoms. Tailored versions of this endpoint were applied to 2 S. aureus BSI trials, and both demonstrated no benefit of the experimental treatment using DOOR and partial credit analysis. Conclusions: Using S. aureus BSI as an exemplar, we developed a DOOR endpoint that can be used as a template for development of DOOR endpoints for other diseases. Future trials can incorporate DOOR to allow for global assessment of patient experience. Abstract : Desirability of outcome ranking (DOOR) evaluates the global benefits and risks of an intervention and provides pragmatic information for medical decision-making. From a survey of infectious diseases experts, a DOOR endpoint for Staphylococcus aureus bloodstream infection was developed and applied to 2 prior trials.